Modular fabrication of intelligent material-tissue interfaces for bioinspired and biomimetic devices - Clegg, John R.; Wagner, Angela M.; Shin, Su Ryon; Hassan, Shabir; Khademhosseini, Ali; Peppas, Nicholas A. (Progress in materials science, 2019)
One of the goals of biomaterials science is to reverse engineer aspects of human and nonhuman physiology. Similar to the body's regulatory mechanisms, such devices must transduce changes in the physiological environment or the presence of an external stimulus into a detectable or therapeutic response. This review is a comprehensive evaluation and critical analysis of the design and fabrication of environmentally responsive cell-material constructs for bioinspired machinery and biomimetic devices. In a bottom-up analysis, we begin by reviewing fundamental principles that explain materials' responses to chemical gradients, biomarkers, electromagnetic fields, light, and temperature. Strategies for fabricating highly ordered assemblies of material components at the nano to macro-scales via directed assembly, lithography, 3D printing and 4D printing are also presented. We conclude with an account of contemporary material-tissue interfaces within bioinspired and biomimetic devices for peptide delivery, cancer theranostics, biomonitoring, neuroprosthetics, soft robotics, and biological machines.